2014
DOI: 10.1186/1471-244x-14-142
|View full text |Cite
|
Sign up to set email alerts
|

Changed processing of visual sexual stimuli under GnRH-therapy – a single case study in pedophilia using eye tracking and fMRI

Abstract: BackgroundAntiandrogen therapy (ADT) has been used for 30 years to treat pedophilic patients. The aim of the treatment is a reduction in sexual drive and, in consequence, a reduced risk of recidivism. Yet the therapeutic success of antiandrogens is uncertain especially regarding recidivism. Meta-analyses and reviews report only moderate and often mutually inconsistent effects.Case presentationBased on the case of a 47 year old exclusively pedophilic forensic inpatient, we examined the effectiveness of a new ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Based on the results of these three case studies, it can be assumed that TLT leads to a decreased activation in brain regions linked with sexual functions, especially with regard to the autonomic, the emotional, and the motivational component of sexual arousal (101)(102)(103). Results of an additional fMRI case study, in which visual sexual stimuli were presented subliminally further indicate that even at an unconscious level, TLT can lead to changes in the processing of sexually relevant stimuli, supposedly reflecting changes in cognitive and perceptive automatic processes (104). Next to fMRI, also eye tracking can be used to depict TLT induced changes.…”
Section: Hormones and Neurotransmittersmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the results of these three case studies, it can be assumed that TLT leads to a decreased activation in brain regions linked with sexual functions, especially with regard to the autonomic, the emotional, and the motivational component of sexual arousal (101)(102)(103). Results of an additional fMRI case study, in which visual sexual stimuli were presented subliminally further indicate that even at an unconscious level, TLT can lead to changes in the processing of sexually relevant stimuli, supposedly reflecting changes in cognitive and perceptive automatic processes (104). Next to fMRI, also eye tracking can be used to depict TLT induced changes.…”
Section: Hormones and Neurotransmittersmentioning
confidence: 95%
“…Next to fMRI, also eye tracking can be used to depict TLT induced changes. In an eye movement study with a single pedophilic CSO who was presented with pedophilic stimuli, it was found that controlled attentional processes could change under TLT whereas automatic processes remained mostly stable (104). Obviously, case studies can only provide anecdotal evidence for the usability of potential biomarkers.…”
Section: Hormones and Neurotransmittersmentioning
confidence: 99%
“…Several studies have shown that CPA, MPA, and GnRH-agonists are all able to reduce sex drive as well as nondeviant and deviant sexual fantasies and behaviors ( Ahn et al, 2013 ; Bradford & Pawlak, 1993 ; Bussmann & Finger, 2009 ; Cooper, 1981 ; Jordan et al, 2014 ; Koo et al, 2014 ; Moulier et al, 2012 ; Rösler & Witztum, 1998 ; Schober et al, 2005 ; Turner et al, 2013 ). Previous meta-analyses about the effectiveness of treatment on the rate of recidivism of individuals who committed sexual offenses have reported medium effect sizes for both hormonal treatments and cognitive behavioral therapy ( Hall, 1995 ; Lösel & Schmucker, 2005 ).…”
Section: Empirical Findings On the Efficacy Of Tlm Treatmentmentioning
confidence: 99%
“… 25 This suggests a key role for T levels in facilitating sexual interest in men. Aside from 1 recent case study of a man receiving AD as treatment for pedophilia, 27 we are unaware of any studies that have directly investigated cognitive processing of sexual stimuli in hypogonadal men. Conversely, men with sexual dysfunction can show decreased visual attention to sexual images, 28 demonstrating that altered sexual cognition also can occur in this population.…”
Section: Introductionmentioning
confidence: 99%